Pengaruh Konsentrasi Methylene Blue dan NaClO pada Proses Degradasi Photocatalytic Fuel Cell Menggunakan Elektroda Cu-TiO2/ZnO - Putri Meylani, Cicilia; Sarah Dampang; Muhammad Fahmi Hakim; Fitri Yuliasari; David Kevin; Tarishah Setyowati Putri (Jurnal Teknik Kimia USU, 2025)
The contamination of synthetic dyes such as methylene blue has become a serious issue in textile industry wastewater due to its resistance to natural degradation. Photocatalytic Fuel Cell (PFC) technology is an effective and environmentally friendly method for degrading toxic dyes in wastewater. In this study, a dual-chamber PFC was developed using a photoanode composed of a Cu-TiO₂/ZnO semiconductor composite synthesized via the sol-gel method. The objective was to develop an efficient composite electrode and evaluate the effect of methylene blue and sodium hypochlorite (NaClO) concentrations on degradation efficiency. The composite was prepared with 5 wt% Cu, calcined at 200 °C, and deposited onto a glass substrate. Characterization using Scanning Electron Microscopy (SEM) revealed that the resulting nanoparticles exhibited a spherical morphology with diameters ranging from 0.22 µm to 4.33 µm. UV-Vis Diffuse Reflectance Spectroscopy (DRS) analysis showed that the band gap energy decreased from 3.18 eV (TiO₂/ZnO) to 2.29 eV after Cu doping. The experimental results demonstrated that the addition of NaClO enhanced the photocatalytic activity of the Cu-TiO₂/ZnO composite for methylene blue degradation, achieving an optimal degradation rate of 78% after 120 minutes of operation.